2001
DOI: 10.1097/00003446-200106000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Steady State Responses to Multiple Amplitude-Modulated Tones: An Optimized Method to Test Frequency-Specific Thresholds in Hearing-Impaired Children and Normal-Hearing Subjects

Abstract: The binaural MF SSR was proven to be a valid technique for the estimation of an objective audiogram, in a large sample of hearing-impaired children and normal-hearing subjects. With this method, frequency-specific thresholds at 0.5, 1, 2, and 4 kHz could be determined in all subjects (and both ears) with no appreciable loss in accuracy and a considerable reduction in testing time (average recording time = 21 minutes) when compared with other frequency-specific techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
52
4
8

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(78 citation statements)
references
References 21 publications
14
52
4
8
Order By: Relevance
“…Similarities in the side or ears -as noted in the present study -have also been reported in the literature 7,[23][24][25] . In the complete series (n = 72 ears) the mean minimum response was 32.4 dBnHL (52.4 dBSPL) at 2 kHz for tone burst ABR in the term and preterm groups.…”
Section: Discussionsupporting
confidence: 91%
“…Similarities in the side or ears -as noted in the present study -have also been reported in the literature 7,[23][24][25] . In the complete series (n = 72 ears) the mean minimum response was 32.4 dBnHL (52.4 dBSPL) at 2 kHz for tone burst ABR in the term and preterm groups.…”
Section: Discussionsupporting
confidence: 91%
“…This was confirmed by the correlation coefficients indicating significantly poorer correlation between behavioural and ASSR thresholds at 0.5 kHz (r=0.31) compared to a high degree of correlation for 1 -4 kHz regions (0.74 -0.88). Although the correlations for the higher frequencies are in close agreement with previously published reports the poor correlation for the 0.5 kHz thresholds are lower than those reported previously [1,4,5,9). This difference may be accounted for to a large extent by the fact that the current sample was confined to moderate hearing losses containing a number of thresholds in the mild hearing loss region for which the ASSR has demonstrated poorer accuracy [8,11,12].…”
Section: Discussionsupporting
confidence: 87%
“…Such differences, smaller than those obtained in the present study, were expected in view of the fact that adolescents or children with hearing loss respond better in tonal audiometry 15 when compared to young children with conductive loss.…”
Section: Resultscontrasting
confidence: 74%